2017
DOI: 10.1016/j.neuroimage.2017.06.006
|View full text |Cite|
|
Sign up to set email alerts
|

Resting-state fMRI correlations: From link-wise unreliability to whole brain stability

Abstract: The functional architecture of spontaneous BOLD fluctuations has been characterized in detail by numerous studies, demonstrating its potential relevance as a biomarker. However, the systematic investigation of its consistency is still in its infancy. Here, we analyze within- and between-subject variability and test-retest reliability of resting-state functional connectivity (FC) in a unique data set comprising multiple fMRI scans (42) from 5 subjects, and 50 single scans from 50 subjects. We adopt a statistica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(59 citation statements)
references
References 43 publications
9
50
0
Order By: Relevance
“…Similar findings have been reported by others as the basis for connectivity-based ‘fingerprinting’ of individuals (Anderson et al, 2011; Finn et al, 2015; Miranda-Dominguez et al, 2014; Pannunzi et al, 2017; Xu et al, 2016). However, the ability to distinguish subjects may at least in part be explained by differences in the spatial locations of brain networks across individuals (Gordon et al, 2017a; Laumann et al, 2015; Satterthwaite and Davatzikos, 2015).…”
Section: Discussionsupporting
confidence: 90%
“…Similar findings have been reported by others as the basis for connectivity-based ‘fingerprinting’ of individuals (Anderson et al, 2011; Finn et al, 2015; Miranda-Dominguez et al, 2014; Pannunzi et al, 2017; Xu et al, 2016). However, the ability to distinguish subjects may at least in part be explained by differences in the spatial locations of brain networks across individuals (Gordon et al, 2017a; Laumann et al, 2015; Satterthwaite and Davatzikos, 2015).…”
Section: Discussionsupporting
confidence: 90%
“…It is important to note that there is an ongoing discussion in the literature regarding whether DFC estimates are largely due to sampling variability versus true changes in FC (e.g. fluctuations in wakefulness) (Pannunzi et al, 2017;Tagliazucchi and Laufs, 2014;Laumann et al, 2017;Haimovici et al, 2017;Liégeois et al, 2017). The present work does not make any claims as to whether DFC estimates reflect dynamics changes in brain functional connectivity as opposed to sampling variability or other artifactual 835 factors.…”
Section: Resultsmentioning
confidence: 71%
“…This is not the first study trying to address reproducibility and consistency in resting state sessions. Many studies have shown that the longer the scanning time is, the better the consistency and reliability of the analysis is (Pannunzi et al, ). Interestingly, some have found that the optimal scanning time to have reproducible results is greater than 14 to 20 min (Anderson, Ferguson, Lopez‐Larson, & Yurgelun‐Todd, ; Birn et al, ; Laumann et al, ), which represents around three to four sessions in the present study, corroborating the idea of a minimal scanning time to have reproducible results.…”
Section: Discussionmentioning
confidence: 99%
“…This represents a major issue given the well-known large anatomical and functional variability across individuals (Frost & Goebel, 2012;Pannunzi et al, 2017). Moreover, functional variability is also expected within a single subject depending on many factors such as the state of the subject and environmental noise (Mueller et al, 2013).…”
Section: Introductionmentioning
confidence: 99%